PENINGKATAN MINAT BELAJAR IPA FISIKA MELALUI PENERAPAN MODEL PEMBELAJARAN PENCAPAIAN KONSEP PADA MATERI KALOR DAN PERPINDAHAN KALOR DI KELAS VII SMP IT MADANI SCHOOL PEKANBARU - Pratiwi1, Wenny Eka Pratiwi Eka; Ma’ruf, Zuhdi Ma’ruf; ', Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study was to describe the interest and increased interest in studying science Physics with the application of the concept model of learning achievement in the matter of heat and heat transfer. The research design used in this study is "Nonequivalent conrol group design" with this type of research quasi experiment. The subjects were students of class VII SMP IT Madani School, which shall be composed of two classes randomly selected as experimental class with 19 students and the number of class control of 19 students. Apply experimental class learning model Achieving control class concept while applying conventional learning models. Data were collected through questionnaires engineering instruments in the form of a questionnaire research interests of students. Data analysis with descriptive analysis techniques to see an increase (gain) interests of students. The results showed an average gain of 0.41 experimental class students' interest (medium category) and the control class 0.36 (medium category). From the comparison of the average gain is about physics student interest in learning IPA science in both classes, indicates that the application of the concept model of learning achievement Physics increase student interest in learning IPA science than the application of conventional learning models. Key Words: Concept Achievement Learning Model , Interest, Gain